Ulam-Hyers Stability of Trigonometric Functional Equation with Involution (Communications in Mathematical Research, 2019)
The present work aims to determine the solution of trigonometric functional equation $f$ with involution from group to field by using the properties of involution function, and the solution and Ulam-Hyers stability of the trigonometricfunctional equation are also discussed. Furthermore, this method generalizes themain theorem and gives the supplement in some reference.